The dirt! : wild life under the soil's surface - Leigh, Lindsey (Penguin Workshop, 2025)
Dig into the often messy world of critters who live underground and learn about why soil is essential to life on earth! Did you know there is an entire ecosystem right beneath our feet? Have you ever heard of the "poop loop"? This graphic nonfiction title will both educate and excite young readers about the wonders (and creepiness!) of animals that live underground, including worms, beetles, armadillos, badgers, and even the tiniest of protozoa. Author and illustrator Lindsey Leigh continues her popular and humorous trilogy by introducing critters of all sizes in this fact-filled book about the dirt-dwelling creatures that contribute to the soil food web and are crucial to the health of the world. Join her on this graphic and grimy deep dive into The Dirt!